Ovarian torsion in infertility treatment - Swapna, Yaramareddy; Elanchezhian, M.; Chegireddy, Supraja; Badipati, Raju; Devadharshini, V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Ovarian torsion, a rare problem in women can lead to serious consequences if not diagnosed and treated at the earliest. It is one of the complications that needs to be included in the differential diagnosis of any girl with abdominal pain or a pelvic or abdominal mass as the symptoms and signs are nonspecific and it can be related to other clinical causes. A 29-year-old woman who was under ovulation induction was diagnosed with ovarian torsion which was treated by performing laparoscopy. Investigations for ovarian torsion should be carried out for all the patients treated for infertility presenting with abdominal pain to minimize the risk before it is too late.